Microalgae-based systems process integration and process intensification approaches - Dias, Rosangela Rodrigues; Jacob-Lopes, Eduardo; Zepka, Leila Queiroz (De Gruyter STEM, 2023)
Process integration and intensification are means to improve the sustainability metrics of the industrial processes, balancing the pillars of economy, environment, and social demand. The book covers a sequential framework for the design and operation of microalgae-based facilities using process integration and intensifi cation, discusses products and applications,and provides a global perspective with contributions from renowned experts. Covers relevant opportunities of process integration and intensification applied tomicroalgae-based systems. Provides a complete review of the state of the art of these industrial approaches. Presents new insights into industrial sustainability